ANALISIS KINERJA EKSPOR DAN IMPOR TEMBAKAU INDONESIA PERIODE 2000-2009 - Luthfi Safitri (Media Ekonomi, 2011)
Writing this thesis aims to find and to anlysis Indonesia tobacco export and import facing global crisis.Based on Indonesia export and impor in 2000-2009. Variabel in this thesis is Indonesia tobacco.Variabel in this thesis in 2000-2009. The method in this thesis is market consentration (KP) Revealed Comparative Advantage (RCA) and Trade Specialization Ratio (TSR). From analysis Regresion in 2000-2009 show that export and import from TSR methode that Indonesia comparative advantages,tobacco can compet with another country in the world.Keywords: Tobacco,Indonesia Expor, Import